1997
DOI: 10.1021/jo971330d
|View full text |Cite
|
Sign up to set email alerts
|

Strain Effects in Protonated Carbonyl Compounds. An Experimental and ab Initio Treatment of Acyclic Carboxamides and Ketones

Abstract: Strain effects have been quantitatively evaluated for a set of 22 compounds including ketones (R(2)CO), carboxamides (RCONH(2)), and N,N-dimethylcarboxamides (RCONMe(2)), where R = Me, Et, i-Pr, t-Bu, 1-adamantyl (1-Ad), in their neutral and protonated forms. To this end, use was made of the gas-phase proton affinities and standard enthalpies of formation of these compounds in the gas phase, as determined by Fourier transform ion cyclotron resonance mass spectrometry (FT ICR) and thermochemical techniques, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…This effect is obviously enhanced by the replacement of a hydrogen by the highly polarizable t ‐butyl group: according to the data reported in Scheme , the increase in PA attains 94 and 73 kJ/mol. Note that the second t ‐butyl group seems to be less efficient since the increase in proton affinity attains only 55 kJ/mol, this may be related to a larger steric repulsion between the two t‐butyl groups in the protonated form (Homan et al, ).…”
Section: Aldehydes and Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is obviously enhanced by the replacement of a hydrogen by the highly polarizable t ‐butyl group: according to the data reported in Scheme , the increase in PA attains 94 and 73 kJ/mol. Note that the second t ‐butyl group seems to be less efficient since the increase in proton affinity attains only 55 kJ/mol, this may be related to a larger steric repulsion between the two t‐butyl groups in the protonated form (Homan et al, ).…”
Section: Aldehydes and Ketonesmentioning
confidence: 99%
“…It will be shown that the basicities of cyclic carbonyl bases increase with the size of the ring. This phenomenon has been interpreted by the combination of two effects (Abboud et al, ; Bordeje et al, ; Homan et al, ; Alcami et al, ). First, the net positive charge located on the carbon atom in canonical structure 1H + b (Scheme ) is extending at the carbonyl substituents (particularly the hydrogen atoms).…”
Section: Introductionmentioning
confidence: 98%
“…(5,30) Strictly speaking, this technique provides standard Gibbs energy changes for reaction (7), rather than the corresponding enthalpies. Fortunately, however, reliable and simple methods exist enabling the correction of the entropy effects.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years one of the aims of our work on thermochemistry has been the quantitative assessment of the structural effects in the gas-phase of acyclic (1)(2)(3)(4)(5) and cyclic carbonyl compounds. (6)(7)(8)(9) The last decade has witnessed important developments in the field of thiocarbonyl chemistry, (10) but as a consequence of the high reactivity of thiocarbonyl compounds, [XC(S)Y], experimentally determined standard enthalpies of formation, f H o m for these compounds are extremely scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This work presents some novelties which can be summarized as follows: (i) for the first time adamantylmethyleneazines have been synthesized; these azines can be used as starting materials for preparing diazapentalenes (criss-cross cycloaddition reaction), 35 2-pyrazolines 36 and many other heterocyclic compounds; 37 (ii) the first x-ray structures of azines bearing adamantyl groups have been reported; recently, there has been much interest in the structure of molecules containing an 1-adamantyl residue, such as Ad-CO-Ad 38 and Ad-NH-COCH 3 , 39 related to the plasticity of adamantane and its derivatives; 40 (iii) A set of novel …”
Section: Discussionmentioning
confidence: 99%